A questão nordestina: Estado, região e futebol - Fernandes, Hévilla Wanderley (2020)
The observation of Brazil’s regional inequalities is the starting point of this survey. The theoretical framework is rooted in Gramsci, analyzing Brazilian reality and its shapes, which will be entitled Northeastern Subalternity, in contrast to the hegemony by the Center and the South of the country. The aim of this study is to expose a historic, politic, economic, social and cultural issue intertwined with the development of Brazilian capitalism and the revolution of the Brazilian bourgeoisie, in other words, the Brazilian Northeastern Question. Hence, categories and concepts of the Italian Marxist Antonio Gramsci will be presented, such as Integral State, Passive Revolution, Intellectuals, and mainly, Hegemony, Subalternity and Southern Question. This research will try "translate" the latter with the intention to comprehend the importance of transposing this issue to the reality of Brazilian Northeast Region, understanding the Class Struggle in this spot. This survey intends to highlight that the Brazilian Northeastern Question, as an issue of this work, is not a static problem. Thus, it is a phenomenon that begins in the early of 20th century and spreads until nowadays, yet not in the same way. The Brazilian Northeastern Question reaches many scopes - political, economic and cultural, among others -, however, this study intends to analyze its influence on soccer, since it is a sport of the masses and one mean of expression of the national culture. In this manner, besides tracing the history of Brazilian Northeast in its multiple frames and the history of Brazilian Northeastern people as a social subaltern group, the path of the most popular sport of Brazil and how it is interconnected with the Northeastern Question will also be traced.